EXPRESSION OF PROTEIN CD73/CD90/CD105/CD34/CD45/CD11b/CD19/HLA-DR ON STEM CELLS FROM HUMAN FAT TISSUE, USING CYTOMETRY FLOW - Imam Rosadi; Karina Karina; Iis Rosliana; Siti Sobariah; Irsyah Afini; Tias Widyastuti; Anggraini Barlian (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2019)
AbstrakSel punca merupakan sel yang dapat membelah dan berdiferensiasi menjadi sel jenis lainnya. Sel punca asal jaringan lemak potensial dikembangkan sebagai salah satu alternatif sel punca yang bersumber dari limbah sedot lemak manusia. Sel punca asal jaringan lemak akan mengekspresikan protein spesifik penanda permukaan CD73, CD90, CD105 dalam persentase yang tinggi dan CD34/CD45/CD11b/CD19/HLA-DR dalam persentase yang rendah. Studi ini bertujuan untuk memanfaatkan limbah sedot lemak manusia dengan melakukan isolasi sel punca asal jaringan lemak dan menguji protein penanda permukaan spesifik sel punca. Beberapa tahapan dalam studi ini adalah isolasi stromal vascular fraction (SVF) dan kultur sel punca asal jaringan lemak manusia, population doubling time (PDT) serta analisis protein penanda permukaan CD7Ee3, CD90, CD105, dan CD34/CD45/CD11b/CD19/HLA-DR pada pasase ke-1 dari 3 donor. Hasil dari studi ini menunjukkan bahwa sel dari jaringan lemak berhasil dikultur dengan durasi pembelahan sel adalah 3,3 hari. Sel mengekspresikan CD73 (99,79%), CD90 (94,17%), CD105 (48,75%), dan CD34/CD45/CD11b/CD19/HLA-DR (kurang dari 2%). Ekspresi CD105 yang rendah dari ketiga donor diduga berkaitan dengan tingkatan pasase sel yang digunakan. Berdasarkan hasil tersebut dapat disimpulkan bahwa sel punca asal jaringan lemak pasase ke-1 telah mengekspresikan ketiga marker protein penanda permukaan sel punca, yaitu CD73, CD90 dan CD105.Abstract Stem cells are cells that can divide into other different types of similar cells. Stem cells from fat tissue potential have been developed as an alternative stem cell from human liposuction. Stem cells from fat tissue will express high protein-specific markers on CD73, CD90, CD105 and CD34/CD45/CD11b/CD19/HLA-DR in a low percentage. This study aims to utilize human liposuction waste by isolating stem cells from fat tissue and testing protein-specific stem cell surface markers. Some stages in this study are isolation of stromal vascular fraction (SVF) and stem cell culture from human fat tissue, population doubling time (PDT) and protein analysis of surface markers CD73, CD90, CD105, and CD34/CD45/CD11b/CD19/HLA-DR on the 1st passage of 3 donors. The results of this study showed that cells from fat tissue were successfully cultured with cell division duration of 3.3 days. Cells expressed CD73 (99.79%), CD90 (94.17%), CD105 (48.75%), and CD34/CD45/CD11b/CD19/HLA-DR (less than 2%). The low expression of CD105 from all three donors is thought to be related to the level of cell passage used. Based on these results, it can be concluded that the stem cells from first passage fat tissue have expressed the three protein markers of stem cell surface markers, namely CD73, CD90 and CD105.